Use of e-cigarettes and smoked tobacco in youth aged 14–15 years in New Zealand: findings from repeated cross-sectional studies (2014–19). (April 2020) - Walker, Natalie; Parag, Varsha; Wong, Sally F; Youdan, Ben; Broughton, Boyd; Bullen, Christopher; Beaglehole, Robert
Summary: Background: Media reports of a vaping epidemic among youth have raised concerns about the creation of a new generation of nicotine-dependent individuals who could graduate to cigarette smoking. We investigated the use of e-cigarettes and cigarettes in the youth of New Zealand from 2014 to 2019, with focus on daily use of these products as an indicator of potential dependence. Methods: We analysed data from the Action for Smokefree 2025 Year-10 survey, an annual cross-sectional survey of tobacco use undertaken by almost half of all school students aged 14–15 years (21 504–31 021 students). The survey includes questions on whether students had ever smoked (even just a few puffs) and their current smoking behaviour (at least once a day, week, or month, or less often than once a month). In 2014, a question was added asking if students had ever tried an e-cigarette. Subsequent surveys asked about e-cigarette use at least once a day, week, or month, or less often than once a month. We compared the frequency of e-cigarette use with cigarette smoking by survey year, age, gender, ethnicity, and school decile (a proxy for socioeconomic status). We did χ 2 analyses to compare categorical variables and Cochran-Armitage trend tests to assess changes over time. Multiple logistic regression was used to determine predictors of e-cigarette and cigarette use in 2019. Findings: All measures of e-cigarette use increased and all measures of cigarette use decreased or remained static over time. Although the proportion of students who had ever tried e-cigarettes in 2019 (37·3%, 10 093 of 27 083), exceeded the proportion who had ever smoked (19·6%, 5375 of 27 354), daily use of products was low: e-cigarettes (3·1%, 832 of 26 532), cigarettes (2·1%, 575 of 27 212), both (0·6%, 159 of 27 633). In 2019, daily use of e-cigarettes was very low in never-smokers (0·8%, 175 of 21 385). Students who were Māori, Pacific, gender diverse, or from low-decile and mid-decile schools were more likely to be daily users of e-cigarettes or cigarettes, and males were more likely to be daily e-cigarette users, but less likely to smoke daily than females. Interpretation: The overall decline in smoking over the past 6 years in New Zealand youth suggests that e-cigarettes might be displacing smoking. Ongoing monitoring will be important to determine whether the liberalisation of e-cigarette availability and marketing in New Zealand has any effect on long-term patterns of daily e-cigarette and cigarette use. Funding: New Zealand Ministry of Health.